Peran Promosi Penjualan “Korean Wave” sebagai Mediator Brand Ambassador dengan Minat Beli Konsumen Produk “Somethinc” - Angelia, Monica; Khouroh, Umu (University of Merdeka Malang, 2023)
This study investigates the effect of brand ambassadors and sales promotion on purchase intention and the mediating role of sales promotion in the relationship between brand ambassadors and purchase intention. The research was conducted through a closed survey and Partial Least Square modeling on a sample of consumers who had used cosmetic “somethinc”. The results of the study show that brand ambassadors do not influence consumers’ purchase intention, on the contrary, sales promotion influences purchase intention positively. Another finding is that sales promotion mediates the relationship between brand ambassadors and purchase intention. Therefore, this paper highlights the importance of paying attention to sales promotions that are used to increase purchasing intention which ends in purchasing decisions. Although the findings of this study are limited to brand ambassadors and sales promotion, this opens the way for further research on this topic, especially regarding the various perceptions of sales promotion carried out and appropriate sales promotion techniques, both among academics and marketing practitioners.